PERAN STRES KERJA DAN DUKUNGAN ORGANISASI TERHADAP KINERJA AWAK BUAH KAPAL (ABK) DI PELAYARAN DOMESTIK - Samekto, Agus Aji (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2024)
This study aims to analyze the effect of work stress and organizational support on the performance of Ship's Crew in the Indonesian domestic shipping sector. Specifically, this research examines the role of organizational support as a moderating variable that can weaken the negative impact of work stress on performance. The seafaring profession is faced with unique and demanding job requirements, including social isolation, long working hours, and a challenging physical environment, which can potentially lead to significant stress and reduced performance. This study adopts a quantitative approach with a causal-explanatory design. The research sample consisted of 125 crew members working in several domestic shipping companies, selected using a purposive sampling technique. Primary data were collected through a Likert-scale questionnaire and analyzed using Multiple Linear Regression Analysis and Moderated Regression Analysis (MRA). The results of the study show three main findings: (1) Work stress has a negative and significant effect on crew performance (β=−0.278,p<0.05). (2) Organizational support has a positive and significant effect on crew performance (β=0.412,p<0.01). (3) Organizational support was proven to significantly moderate the relationship between work stress and performance (β=0.195,p<0.05), where the negative influence of work stress on performance becomes weaker at high levels of organizational support. This study concludes that organizational support not only functions as a performance driver but also as a vital protective mechanism in mitigating the adverse effects of stress in the high-pressure maritime work environment. The practical implication is that shipping companies need to strategically invest in building a strong organizational support system as an integral part of safety management and human resource performance improvement.